2017
DOI: 10.6018/analesps.34.1.229571
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Self-Efficacy, Anxiety, Attitudes and Mathematics Achievement Regarding Gender and School Type

Abstract: Título: Investigando la autoeficacia, la ansiedad, las actitudes y los logros de las matemáticas con respecto al género y el tipo de escuela. Resumen: El propósito de este estudio fue investigar la relación entre la autoeficacia en matemáticas, la ansiedad en matemáticas, la actitud con respecto a matemáticas, el rendimiento en matemáticas de los estudiantes del séptimo grado y el género y el tipo de escuela. Con el fin de examinar la diferencia en la autoeficacia, la ansiedad la actitud y el rendimiento en cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
5
12

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 38 publications
4
45
5
12
Order By: Relevance
“…The results of this study are similar to the research conducted by Çatlioglu et al (2009); Dane (2005); Haynes et al (2004); Peker & Ertekin (2011) which shows that there is no difference in MA between women and men. Unlike the results of this study, the results of other studies show that there are differences in MA between women and men, where MA in women is greater than men (Bowd & Brady, 2003;Goetz, Bieg, Lüdtke, Pekrun, & Hall, 2013;Gürbüz & Yıldırım, 2016;Hembree, 1990;Hill et al, 2016;Recber, Isiksal, & Koç, 2018). Meanwhile, Burak & Ozel (2012) in their study states that male has a higher MA than female.…”
Section: The Difference In Ma Between Female and Male Pre-service Elecontrasting
confidence: 92%
“…The results of this study are similar to the research conducted by Çatlioglu et al (2009); Dane (2005); Haynes et al (2004); Peker & Ertekin (2011) which shows that there is no difference in MA between women and men. Unlike the results of this study, the results of other studies show that there are differences in MA between women and men, where MA in women is greater than men (Bowd & Brady, 2003;Goetz, Bieg, Lüdtke, Pekrun, & Hall, 2013;Gürbüz & Yıldırım, 2016;Hembree, 1990;Hill et al, 2016;Recber, Isiksal, & Koç, 2018). Meanwhile, Burak & Ozel (2012) in their study states that male has a higher MA than female.…”
Section: The Difference In Ma Between Female and Male Pre-service Elecontrasting
confidence: 92%
“…This finding is consistent with the study conducted by Ayotola and Adedeji (2009) which found no significant statistical difference in the mathematics self-efficacy of male and female students. However, the result contradicts the findings of Louis and Mistele (2012), Recber et al (2018), and Eccles et al (1993) which concluded that female students displayed higher self-efficacy than male students and Zhang et al (2015) which found that male students had higher self-efficacy than their female counterparts.…”
Section: Discussioncontrasting
confidence: 79%
“…On the other hand, only the most popular lesson on the attitude towards mathematics lesson was found meaningful. Recber, Isiksal & Koç (2018) reported that gender being among the independent variables of this study is an important predictor of attitudes, anxiety and success towards mathematics. Devine, Fawcet, Szucs & Dowker (2012) found that gender did not significantly differentiate mathematics performance, whereas women's math anxiety was higher than men.…”
Section: Conclusion Discussion and Suggestionsmentioning
confidence: 68%